Topoisomerase 1-mediated Removal of Ribonucleotides from Nascent Leading Strand DNA - Williams, Jessica S. (2013)
RNase H2-dependent Ribonucleotide Excision Repair (RER) removes ribonucleotides incorporated during DNA replication. When RER is defective, ribonucleotides in the nascent leading strand of the yeast genome are associated with replication stress and genome instability. Here we provide evidence that topoisomerase I (Top1) initiates an independent form of repair to remove ribonucleotides from genomic DNA. This Top1-dependent process activates the S phase checkpoint. Deleting TOP1 reverses this checkpoint activation and also relieves replication stress and genome instability in RER-defective cells. The results reveal an additional removal pathway for a very common lesion in DNA, and they imply that the “dirty” DNA ends created when Top1 incises ribonucleotides in DNA are responsible for the adverse consequences of ribonucleotides in RNase H2-defective cells.